Factors affecting repurchase intention with customer engagement as intervening variables in B2B context - Negina Kencono Putri; Arief Wisnu Wardhana (Mednarodno Inovativno Poslovanje)
Purpose: The goal of this research is to learn more about the impact of customer satisfaction., social CRM, customer perceived value, on repurchase intention. This research is survey research on consumers of construction companies specifically in this case manufacturing companies in Indonesia.